2023
DOI: 10.31616/asj.2022.0358
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Intravenous Nefopam on Pain Management and Ambulation after Open Spine Surgery: A Randomized Double-Blind Controlled Study

Abstract: Study Design: This was a randomized double-blind controlled study.Purpose: This study was designed to evaluate the effects of intravenous nefopam regarding its ability to reduce morphine consumption and postoperative pain and improve recovery in patients undergoing open spine surgery.Overview of Literature: Multimodal analgesia, including nonopioid medications, is essential for pain management in spine surgery. Evidence regarding the use of intravenous nefopam in open spine surgery as part of enhanced recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…Some studies have reported that nefopam did not reduce PCA or opioid consumption during the first 3 d post-operation [31][32][33]. In contrast, another study found that the group treated with nefopam experienced less pain during ambulation and had a shorter hospitalization period than the control group [12]. In our study, the nefopam group reported reduced postoperative pain; however, the difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Some studies have reported that nefopam did not reduce PCA or opioid consumption during the first 3 d post-operation [31][32][33]. In contrast, another study found that the group treated with nefopam experienced less pain during ambulation and had a shorter hospitalization period than the control group [12]. In our study, the nefopam group reported reduced postoperative pain; however, the difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 90%
“…Several studies investigating various types of surgeries, including abdominal, thoracic, and orthopedic procedures, have documented that nefopam reduces acute postoperative pain and exhibits an opioid-sparing effect [9][10][11][12]. Recently, there has been growing attention paid to the role of nefopam in neuropathic pain [13].…”
Section: Introductionmentioning
confidence: 99%